2012
DOI: 10.1021/nl3012038
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Planet–Satellite Analogues: Hierarchical Self-Assembly of Gold Nanostructures

Abstract: In the past few years, a remarkable progress has been made in unveiling novel and unique optical properties of strongly coupled plasmonic nanostructures, known as plasmonic molecules. However, realization of such plasmonic molecules using nonlithographic approaches remains challenging largely due to the lack of facile and robust assembly methods. Previous attempts to achieve plasmonic nanoassemblies using molecular ligands were limited to dipolar assembly of nanostructures, which typically results in polydispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
200
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(204 citation statements)
references
References 31 publications
3
200
0
1
Order By: Relevance
“…There are various strategies for the realization of hot spots, e.g., aggregation of NPs, satellite-systems [25,26], nanostructures fabricated by electron-beam lithography (EBL), and focused ion beam (FIB) milling. However, colloids aggregation is unpredictable random process that leads to alternating Raman enhancement and decreased reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…There are various strategies for the realization of hot spots, e.g., aggregation of NPs, satellite-systems [25,26], nanostructures fabricated by electron-beam lithography (EBL), and focused ion beam (FIB) milling. However, colloids aggregation is unpredictable random process that leads to alternating Raman enhancement and decreased reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported a novel class of shape-controlled plasmonic nanostructures, namely, core-satellite structures, which was achieved through self-assembly using simple molecular cross-linkers (see fig. 11.5) [16].…”
Section: Plasmonic Engineeringmentioning
confidence: 98%
“…Several computational and experimental studies have clearly demonstrated that the SERS Ef at these EM hot spots is upward of 10 8 , which is nearly four to six orders of magnitude higher than the corresponding individual nanostructures [16,54]. Despite significant efforts toward controlled assembly of plasmonic nanostructures, realizing scalable nanoparticle assemblies that offer highly uniform, isotropic, and stable SERS enhancement remains challenging.…”
Section: Plasmonic Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Neben dem menschlichen Streben nach äs-thetischen und geordneten Strukturen ist die Untersuchung der resultierenden physikalischen Eigenschaften solcher Systeme eine weitere Triebkraft in diesem Forschungsgebiet, die unter anderem zu Planet-Satellit-Nanostrukturen geführt hat. Diese Materialien wurden als Elemente für die Sensorik, [2] Hilfsgerüste zur selektiven Funktionalisierung von Nanopartikeln an spezifischen Halbseiten, [3] plasmonische Messbänder, [4] Substrate für die oberflächenverstärkte Raman-Streuung [5] und Agentien für den tumorspezifischen Wirkstofftransport [6] vorgeschlagen. Eine effiziente und flexible Syntheseroute zu Planet-Satellit-Strukturen ist jedoch Voraussetzung für die Erforschung und Verwendung dieser Architekturen.…”
unclassified